A new instrument for assessing the quality of studies on prevalence - Giannakopoulos, Nikolaos Nikitas; Rammelsberg, Peter; Eberhard, Lydia; Schmitter, Marc (Clinical oral investigations, 2012)
There are numerous scientific articles of studies on the prevalence of disorders with non-standardised examination and diagnostic protocols. Because their quality is heterogeneous, a new instrument has been developed for the assessment of such studies. The new instrument is based mainly on statistical criteria. The points assigned for each of the main criteria according to the information gained from each paper are summed up to form a Total Quality Score (TQS). The interrater reliability of the instrument was tested by employing Kappa and Interrater Correlation Coefficient (ICC) statistics. The latter was assessed on the results of three independent investigators. The new quality instrument appeared to be easy to use, and the instructions were comprehensible. The ICC(2,1) for the TQS ranged between 0.94 and 1.00 indicating almost perfect agreement between the investigators. The reliability of the new instrument enables its use for scientific review purposes. In this way, its validity will also be tested. The instrument could be adopted for assessment of scientific articles of studies on the prevalence of disorders in many, similar, scientific areas.